Project-Based Learning with or Without Multimodal Features: Action-Based Research for Developing and Assessing Intercultural Competence (European Journal of Teaching and Education, 2023)
The present paper proposes a framework for using "Multimodal Creative Projects" (MCP) for developing intercultural competence in engineering students. Instructors added a multimodal feature to improve students' learning experiences while engaging them in project-based learning. This feature provided numerous opportunities for multiple representations of content to students using text, video, audio, images, and comic strips that suited their diverse learning styles. We argue that, though both academic research paper writing and MCP, allow an instructor to carry out an assessment of learning as well as an assessment for learning, it is MCP that improves learner motivation, engagement, and learning outcomes better when compared to academic research paper writing. For collecting data for the study, a questionnaire was designed and circulated using Google Forms to 122 engineering students enrolled in the Cross-Cultural Skills course, being offered at the Birla Institute of Technology and Science, India, a premier engineering institute in India. The findings of the experiment indicate that the majority of the students who opted for MCP-based assignments found their mode of learning to be effective in making use of their core and creative skills and also providing flexibility, which enhanced their interest, engagement, and learning performance in the course.